Mechanisms of vessel pruning and regression - Korn, Claudia; Augustin, Hellmut (Developmental cell, 2015)
The field of angiogenesis research has primarily focused on the mechanisms of sprouting angiogenesis. Yet vascular networks formed by vessel sprouting subsequently undergo extensive vascular remodeling to form a functional and mature vasculature. This “trimming” includes distinct processes of vascular pruning, the regression of selected vascular branches. In some situations complete vascular networks may undergo physiological regression. Vessel regression is an understudied yet emerging field of research. This review summarizes the state-of-the-art of vessel pruning and regression with a focus on the cellular processes and the molecular regulators of vessel maintenance and regression.